Antibacterial activity of Blumea axillaris synthesized selenium nanoparticles against multidrug resistant pathogens of aquatic origin. Issue 1 (31st December 2022) - Dash, Jyoti Prakash; Mani, Lopamudra; Nayak, Sukanta Kumar
ABSTRACT: Selenium one of the most important trace elements exhibits diverse biological functions. Particularly in fishes, it plays a protective role and enhances growth performances. The green synthesized selenium nanoparticles have added benefits including ease of availability, economic, safe, etc. Furthermore, the development of multidrug-resistant pattern among pathogens in general and aquatic pathogens in particular has raised the demand for a potential substitute for regularly used antibiotics . Hence, this study was intended to synthesize selenium nanoparticles in a green route method from sodium selenite salt by using the plant Blumea axillaris and to evaluate their antibacterial activity against aquatic pathogens. The findings of this study indicated that the stem and root of B. axillaris were capable of synthesizing selenium nanoparticles with an optimised salt concentration of 0.1 M. Further both the stem and root extracts synthesized selenium nanoparticles were found to inhibit pathogens. While aquatic pathogens exhibited multidrug resistance pattern against many commonly used drugs, the green synthesized selenium nanoparticles were found to effectively control these pathogens. However, the detailed study on the mechanism of inhibition is going on which in turn can be a very cheap, safe, and economical way of enhancing aquaculture industry.